Pelatihan Pembuatan Peraturan Desa Wisata di Desa Kemiri Kabupaten Jember - Emy Kholifah R; Baktiawan Nusanto (Journal of Community Development, 2022)
This service aims to conduct training for stakeholders in Kemiri village, Jember Regency. These stakeholders are the village head, and the ranks of the village apparatus, the head of the BPD and members of the BPD. The background of this community service is the high need from stakeholders for insight and skills in the village policy-making process. Kemiri Village, which was inaugurated by the Regent of Jember as a tourism village, demands the ability of stakeholders to develop candlenut tourism villages. The development of tourist villages can be achieved starting from the political commitment of these stakeholders. This political commitment is a political policy as outlined in the village government regulation (PERDES). Thus the solution to this need is training and assistance in making village regulations in an effort to develop Kemiri tourism villages. The framework of thinking/content in the training of making village regulations refers to a rural based development approach, where village development includes the idea that village development is carried out to increase the benefits of natural potential, community potential, social institutional potential and local economic potential and local culture, as well as potential government apparatus to support the development of tourist villages. Kemiri Village, which has the characteristics of a mountainside village (Gunung Argopuro), the direction of its development has the potential for natural beauty, the potential of agriculture-plantation through processing agricultural products, and the unique culture of the community community and various other local wisdoms that can become social capital for the development of tourist villages. However, this great potential should continue to be explored so that it can become a real asset, for that, the involvement of various parties who have empathy and a vision of village development should synergize the roles of one another. The partnership between village stakeholder groups and higher levels of government, DUDI (industrial world business), private groups, and groups of scholars from universities (students and lecturers who carry out BKP-MBKM Village Development) is the key phrase for accelerating tourism village development. . This line of thought was built so that training and mentoring can be right on target and in accordance with the potential of the village area on the slopes of Mount Argopuro (especially Kemiri Village). This community service will involve students who are doing BKP-MBKM in Kemiri village.